Comparison of Outcomes of Cheilectomy with and without Synthetic Hydrogel Interposition (Cartiva®). Issue 4 (22nd October 2020) - Ford, Samuel E.; Scott, Daniel J.; Alejandro, Shannon F.; Vier, David D.; Zide, Jacob R.; Brodsky, James W.
Category: Midfoot/Forefoot; Other Introduction/Purpose: Cheilectomy and arthrodesis are the primary surgical treatments of hallux rigidus. While cheilectomy preserves limited motion, that motion can be the source of persistent pain that later requires arthrodesis. Cheilectomy with interposition arthroplasty using a synthetic hydrogel implant (Cartiva) has been proposed as an alternative to arthrodesis. Previous studies compared Cartiva to arthrodesis, but Cartiva is really a modification of cheilectomy, meant to improve its results by distracting the bony surfaces of the first MTP joint. This study compared outcomes of cheilectomy with Cartiva to cheilectomy alone. Methods: A retrospective cohort study assessed the results at 1-year minimum follow-up, identifying patients by CPT code for cheilectomy with (28291) and without (28289) Cartiva interposition. There were forty-five patients: 26 in the Cartiva group and 19 in the cheilectomy group. Tabulated data included: age, gender; preoperative, 6-month, and final postoperative total first MTP ranges of motion (ROM); preoperative and final postoperative VAS and SF-36 scores; and reoperation information. Hallux rigidus grade was assessed by Coughlin and Shurnas criteria. First MTP joint space was measured at the medial, midline, and lateral portions of the joint on both AP and lateral radiographs before, immediately following, and at maximum postoperative follow-up (16 month mean). For analysis, medial, midline, and lateral joint measurements were averaged to generate a composite measure of radiographic joint space. Follow-up means were 23 months for all patients, 18 for Cartiva and 28 for cheilectomy. Results: Mean age was 54. Mean preoperative grade was 2.6 for Cartiva and 2.1 for cheilectomy (p=0.037). Mean preoperative ROM was 44°. At 1 year follow-up, ROM was 39° for Cartiva and 47° for cheilectomy (p=0.95). Mean VAS improved from 5.8 to 2.0 and 3.0 for Cartiva and cheilectomy, respectively, at final follow-up (p=0.002, p=0.004). Following Cartiva, two week postoperative joint space means increased: AP midline 1.4 to 2.6 mm, AP composite 1.4 to 2.2 mm, and lateral midline 1.3 to 2.7 mm (p<0.001). At final follow-up, joint space measures returned to levels similar to cheilectomy: AP midline 1.3 vs. 1.2 mm, AP composite 1.1 vs. 1.2 mm, and lateral midline 1.6 vs. 1.2 mm (p>0.3). Five patients in each group (22%) underwent revision. Conclusion: Cartiva offers similar intermediate-term ROM preservation and pain relief as cheilectomy in a cohort with higher grade hallux rigidus. Joint distraction gained by synthetic hydrogel interposition subsides with time to levels similar to cheilectomy. Revision surgery for persistent pain is common in both groups.